Poverty Impact of the Economic Slowdown in Developing Asia: Some Scenarios - Rana Hasan; Maria Rhoda Magsombol; J. Salcedo Cain (Asian Development Bank (ADB), 2009)
This paper uses the empirical relationship between economic growth and poverty reduction observed between 1990 and 2005 and different scenarios for economic growth to get a sense of how the economic slowdown in the region will affect the incidence of poverty. Since most countries that we work with in this paper experience an increase in gross domestic product per capita even under our "low growth" scenario, poverty in developing Asia continues to decline in 2009 and 2010. What gets adversely affected, however, is the pace of poverty reduction. In particular, our estimates indicate that a reduction in growth of GDP per capita of 3 percentage points over growth registered in 2007 - a year of high growth for many Asian developing countries - would result in almost 61 million additional 1.25/day poor in 2009 and 98 million additional poor in 2010 as compared to a baseline scenario of no economic slowdown.
hdl:11540/1808
Keywords: 330; Armut; Wirtschaftswachstum; Verteilungswirkung; Entwicklungsländer; Asien